Clotting Activation and Hyperfibrinolysis in Cirrhosis: Implication for Bleeding and Thrombosis - Violi, Francesco; Ferro, Domenico (Seminars in Thrombosis and Hemostasis, 2013)
Hyperfibrinolysis may be detected in patients with cirrhosis, particularly in case of severe liver failure. Hyperfibrinolysis is usually associated with prolonged global tests of clotting activation, which are then dependent on impaired synthesis of clotting factors by liver cells. The term “coagulopathy” has therefore been coined to indicate the existence of hyperfibrinolysis and blood hypocoagulation in cirrhosis, and, for a long time, these changes have been believed to facilitate bleeding. However, apart from gastrointestinal bleeding, which is related prevalently to hemodynamic factors in the portal circulation, spontaneous bleeding is less frequent than would be expected by the abnormality of laboratory tests. This apparent paradox may be explained by studies questioning the term “coagulopathy,” instead documenting a hypercoagulation state in portal as well as in peripheral circulation of cirrhotic patients. The support of these findings by more recent data allows a redefinition of the overall clotting picture, in particular hyperfibrinolysis, in cirrhosis. Thus, this review analyzes prevalence and clinical impact of hyperfibrinolysis in cirrhosis, focusing in particular on whether it is primary or secondary to clotting activation. Furthermore, we focused such changes in the context of more recent data showing an association between cirrhosis and thrombosis.
Keywords: liver cirrhosis; hyperfibrinolysis; portal vein thrombosis; anticoagulants